Relationship between Spirituality and Acceptance of Illness Level in Bipolar Patients - Atsira, Olga Putri; Yuliati, Erikavitri; Atika, Atika; Abdurachman, Abdurachman; Maramis, Margarita Maria (UI Scholars Hub, 2020)
Bipolar disorder is a chronic mental condition that affects patients’ quality of life. The management process is affected by acceptance of illness. The ability to accept the illness is related to the spirituality level which is something that is held strongly by Indonesian people. There has been very little research related to the relationship between spirituality with bipolar disorder. This study aimed to analyze relationship between spirituality levels with acceptance of illness in patients with bipolar disorder. This study is a correlational study using questionnaire from bipolar disorder patients contacted through Harmony in Diversity online community as a sample. Samples were taken in total sampling according to inclusion and exclusion criteria. The numbers of samples were 30 samples. Calculation of the correlation between acceptance of illness in patients with bipolar disorder with vertical spirituality (RWB) (p = 0.050) (r = 0.306), horizontal spirituality (EWB) (p = 0.001) (r = 0.556), and general spirituality (SWB) (p = 0.007) (r = 0.444). There is a significant positive correlation between acceptance of illness in patients with bipolar disorder and general spirituality with a more significant horizontal dimension compared to vertical dimension.